An Ecosystem Approach to Knowledge Management - Chang, Vanessa; Tan, Amanda (Springer, 2012)
Effective use of knowledge in organisations would typically lead to improved organizational performance. Organisations that practice and leverage organizational knowledge through integration, innovation and sharing of lessons learned will continue to improve and strengthen the organisation’s operation. The ecosystem approach described in this paper centred on the premise that knowledge is individualised information enriched through the process of learning, then shared and applied to practical situations. To capture better knowledge management, a collaborative knowledge management framework is used to examine the positions of knowledge management in an organisation. To highlight the complex and heterogeneous nature of knowledge management, a set of practices aimed to enhance collaboration is presented as holistic approach toward improving practical learning environments. In addition, a set of actionable knowledge management strategies to improve the relationships among the components interacting within each organisational ecosystem can be recommended as a result of using the framework.